Management of Psychosocial Risks Associated with Participation in Physical Activities - Nwankwo, Gloria O.; Alaubi, Stanley C. (Archives of Business Research, 2023)
The purpose of this paper is to establish that participation in physical activities has the potential to expose participants to psychosocial risks. It outlined the psychosocial risks that participants in physical activities are prone to and represented them with SCREAS as an acronym for Scheduling, Component, Relationship, Environment, Addiction and Substance abuse. It highlighted how participants are exposed to these risks. It concluded by stating that although participation in physical activities is accepted lifestyle but studies have shown that it has the potential to expose participants to various risks. Participation in physical activities is one choice that can move an individual from one risk to another if the risks are not properly identified, assessed, controlled and effectively managed. It recommended among others that physical activities should be organized by professionals in exercise science and safety for effective management of risks associated with physical activities and participants should be guided at every stage of participation and counselled where necessary.